Electronic customer relationship management system for event management industry "How an e-CRM system can be used in the sales process" - Mohd Nor, Suzyhazra (2005)
This study examines the needs of Electronic Customer Relationship Management system in the Event Management industry. There are a lot of Event Management agencies in Malaysia offering event management service to individual or organization who wants to held but these agencies are not popular because of slow communication flow between customer, Event Management agent and event space provider. An interview method was applied to the selected organization which known as Exhibitions Promotion & Management (M) Sdn Bhd in order to ascertain the present Event Management method and the perceptions of how e-CRM can be use in their sales process. E-CRM highlights the importance of using Information Technology in creating, maintaining and enhancing customer relationships. Thereby, the purpose of this study is to describe e-CRM and the realization of CRM in event management industry by using e-CRM system. The research in this study can be considered as both exploratory and descriptive but mainly explorative. The analysis is based on the empirical findings, as well as on the theoretical framework for this study. The analysis shows that the goal with e-CRM is to maximize company profits by maximizing the value of interaction with the customers. In order to do this, companies need a business strategy that focuses on the customers and that generates a process oriented view of the organization. The business processes needs to be supported by e-CRM system, comprising e-CRM functionality that makes it possible to create a single view of the customer as well as of the company. The analysis also shows that the stage in the e-CRM development process affects a company's view on e-CRM. In order to describe how event management industry can be use e-CRM system, this study includes a description of how e-CRM functionality can be used at different steps in the sales process. Certain functionality is generally applicable and can be used at many different steps in the sales process, while some functions can be connected to a specific step. The analysis shows that the functionality included in the three main functionality categories are used in all phases in the sales process. Consequently, the connection between e-CRM functionality and the sales process gives a complete view on how e-CRM system can be used.